Relações entre grandezas geométricas: um estudo de caso baseado na aprendizagem significativa e análise de erros - Both, Mateus (2016)
This work had as objective investigate the subsumer about the concept of variation that exist on the Mathematics freshmen’s, as propose alternatives that could lead to a meaningful learning about it. It has also aiming evaluate the happening of meaningful learning based on the analysis and classification of the mistakes made by the freshman’s in 2015 with the Model of Didactic Error Analysis (MADE). The mistakes were made during the resolution of the proposal questions to the participants, this questions required previous knowledge about geometrical quantities. From that analysis it was elaborated an activity supposed to be potential meaningful based on the Meaningful Learning Theory (TAS), which also evolved the Virtual Ambient of Learning and Teaching (AVEA) Moodle and the software GeoGebra. This research has a quanti-qualitativy feature and the instruments it used were questionnaire, diagnostic test, interview, investigative activity and evaluation. Beyond the error analysis, we realized interviews for a better comprehension and enhancement from the students profile and the reasons for the answers given in the diagnostic test. This research was divided in 4 parts. In the first one, it was realized the application of one questionnaire and the diagnostic test to accomplish the difficulty survey, made of 5 questions, with 24 students. On the second part, it was proposed the development and application of a potential meaningful instructional material with the Calculo I students during the second semester from 2015. However for the analysis of the potential meaningful activity and comparation from the students’ results we consider only those how had attend the diagnostic test. At the same time we realized interviews with 9 students. The freshman’s were chosen because they had just finished high school which implies they belong to a transition process between school/university in a knowledge level. On the third part, was applied an evaluated question, aiming to verified the development and learning from the students. In the end, on the fourth part, after and during the application of the activity, was realized an evaluation of the efficiency and applicability of the material, with the goal of seeking for evidence about meaningful learning and/or possibilities of re/construction from the basics subsumer concepts related to geometric quantities.